Tenacity of Bacillus cereus and Staphylococcus aureus in dried spices and herbs. (January 2018) - Dinh Thanh, Mai; Frentzel, Hendrik; Fetsch, Alexandra; Krause, Gladys; Appel, Bernd; Mader, Anneluise
Abstract: Numerous studies examined the antimicrobial effects of spice and herb extracts, whereas little is known about the effects of dry condiments on the survival of microorganisms. This study investigated the impact of dried condiments on the survival of Bacillus cereus and B. thuringiensis spores as well as Staphylococcus aureus cells. In addition, the survival variability between different strains was evaluated. Condiments (allspice, basil, cinnamon, nutmeg, oregano, paprika, parsley and pepper) were artificially contaminated by a dry spiking method using sand as carrier matrix and as control. The results show that counts of B. cereus and B. thuringiensis spores (initial spore count 5.6 ± 0.2 log10  cfu/g and 6.7 ± 0.1 log10  cfu/g, respectively) did not decline significantly in all condiments over a period of 50 weeks. In contrast, in some of the spiked test materials, cell counts of S. aureus (initial cell count 8.1 ± 0.5 log10  cfu/g) were reduced below the detection limit of 10 cfu/g within 10 weeks of storage. D values for S. aureus ranged between 5 and 31 days depending on the strain, condiment and initial contamination level. In conclusion, dried condiments may not affect the survival of spores but can significantly affect the survival of non-spore forming bacteria. As strain variability can occur, tenacity studies should be conducted including a variety of strains. Highlights: B. cereus spore counts did not decline significantly over 50 weeks in condiments. S. aureus counts declined below the detection limit after 5 to more than 20 weeks. Matrix effects could be found for S. aureus, but not for Bacillus strains. Some differences between the four tested S. aureus strains could be detected.